Public Governance Orchestration and Politics Agenda in Implementing Indonesia’s Nutritious Meal Program - Ismunarta (Politicon : Jurnal Ilmu Politik, 2025)
The Free Nutritious Meal (MBG) programme offers significant nutritional and socio-economic potential, yet implementation weaknesses undermine its projected benefits. An ex-ante cost–benefit analysis over a five-year horizon (6% discount rate) estimates a net present value of IDR 439.26 trillion and a benefit–cost ratio of 1.76, but also reveals annual waste and loss of around IDR 47.18 trillion. To explain this gap between economic potential and field realities, a qualitative documentary analysis, guided by the innovation network orchestration framework, identifies four main governance barriers: fragmented and outdated beneficiary data, intermediary-controlled information flows limiting learning and verification, weak procedural justice and grievance systems, and the absence of collective incentive structures for fair value capture. These deficits reduce knowledge mobility and weaken innovation appropriability, converting theoretical gains into real losses. The study proposes a governance architecture integrating national databases, provincial command centres, and PKH-style transfer mechanisms (escrow payments, contractual SLAs, audit trails) to secure targeting, enable real-time monitoring, and embed feedback loops. Framed as post-populist orchestration, this approach aims to align political momentum with evidence-based delivery. The paper concludes that MBG’s viability depends on sequenced governance reforms, recommending pilot implementation with process tracing and impact evaluation to validate its effectiveness.